2023
DOI: 10.1111/wbm.12262
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide‐resistant barnyardgrass (Echinochloa crus‐galli) in global rice production

Abstract: Barnyardgrass (Echinochloa crus-galli (L.) Beauv.), an annual species of the family Poaceae, is a major weed problem in rice-producing countries throughout the globe. Synthetic herbicides can effectively control this grass in rice paddies, but the development of resistant biotypes after the continuous use of the same active ingredients has led to low herbicide efficacy and yield losses. In this review, a summary of resistant-barnyardgrass cases in global rice production is reported based on data from the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Echinochloa crus-galli is a common and noxious weed in crop production worldwide. 11 The species is classified into multiple varieties, for example, E. crus-galli var. crus-galli and var.…”
Section: Introductionmentioning
confidence: 99%
“…Echinochloa crus-galli is a common and noxious weed in crop production worldwide. 11 The species is classified into multiple varieties, for example, E. crus-galli var. crus-galli and var.…”
Section: Introductionmentioning
confidence: 99%
“…Fenoxaprop- p -ethyl is an aryloxyphenoxypropionate herbicide that inhibits the ACCase enzyme and is used in rice fields to control grasses, especially E. crus-galli. , Because of the narrow spectrum of control, it is often used in a tank mix with different herbicide modes of action to provide a wider weed control spectrum. , Imazethapyr is an ALS inhibitor used in imidazolinone-tolerant rice varieties with efficacy on grasses, sedges, and broadleaves; however, resistance to imazethapyr has occurred in several rice areas worldwide, , and the mechanism of resistance is often associated with enhanced herbicide metabolism. ,, The herbicide mixture of fenoxaprop-p-ethyl and imazethapyr is a common practice by rice farmers to control resistant barnyardgrass biotypes; however, some studies showed that this mixture is often antagonistic. , The consequences of herbicide mixture applications over multiple years on herbicide resistance evolution in weeds are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Imazethapyr is an ALS inhibitor used in imidazolinone-tolerant rice varieties with efficacy on grasses, sedges, and broadleaves; 38 however, resistance to imazethapyr has occurred in several rice areas worldwide, 10,39 and the mechanism of resistance is often associated with enhanced herbicide metabolism. 32,39,40 The herbicide mixture of fenoxaprop-p-ethyl and imazethapyr is a common practice by rice farmers to control resistant barnyardgrass biotypes; however, some studies showed that this mixture is often antagonistic. 15,37 The consequences of herbicide mixture applications over multiple years on herbicide resistance evolution in weeds are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, molecular analyses have provided recent insights into its evolution as a weed (Guo et al 2017; Wu et al 2022). Recently, global cases of herbicide resistance in barnyardgrass were reviewed (Damalas and Koutroubas 2023). With special reference to barnyardgrass, this article aims to 1) highlight the current state of knowledge on economically relevant Echinochloa species in U.S. rice production in terms of their introduction and persistence/adaptation in U.S. rice agroecosystems, provide a historical overview of their management and emerging herbicide resistance issues; and 2) identify the research needs for their sustainable management in U.S. rice on the cusp of a paradigm shift in weed management approaches.…”
Section: Introductionmentioning
confidence: 99%